215 Ticagrelor Inhibits Release of Pro-inflammatory Cytokines TNF and IL-6 during Human Endotoxaemia. (31st May 2014) - Thomas, Mark; Judge, Heather; Dockrell, David; Sabroe, Ian; Storey, Robert
Abstract : Introduction: In the PLATelet inhibition and patient Outcomes (PLATO) study, ticagrelor was associated with fewer pulmonary infection events and subsequent deaths but slightly higher inflammatory markers compared to clopidogrel. Ticagrelor and clopidogrel inhibit platelet P2Y12 receptors via different mechanisms and ticagrelor additionally is a weak inhibitor of reuptake of adenosine, which has numerous effects on innate immunity. We studied the effects of ticagrelor and clopidogrel on the innate immune responses of healthy volunteers. Methods: 30 healthy volunteers were randomised to receive ticagrelor 90 mg bd (n = 10), clopidogrel 75 mg od (n = 10) or no antiplatelet medication (controls; n = 10) for one week. E. coli endotoxin (LPS, 2 ng/kg) was then administered intravenously. Blood was sampled pre-treatment, after treatment and over 24 h post LPS. Platelet aggregation induced by 30 µM ADP was assessed by optical aggregometry. Platelet P-selectin expression and platelet-leukocyte conjugate formation were determined by flow cytometry. Plasma levels of cytokines were determined using cytometric bead array. Results: After treatment, maximal platelet aggregation responses to ADP in the ticagrelor, clopidogrel and control groups were 12 ± 6%, 31 ± 26% and 81 ± 24% respectively. After LPS exposure, ticagrelor and clopidogrel significantly reduced ADP-induced platelet P-selectin expression and platelet-monocyte conjugate formation compared to controls. LPS-induced increases in TNF were significantly attenuated by both ticagrelor (p = 0.025) and clopidogrel (p = 0.017), which reduced peak levels by 61% and 60% respectively compared to controls. Peak TNF levels correlated with indices of platelet reactivity (ADP-induced platelet aggregation [p = 0.0096], P-selectin expression [p = 0.026] and platelet-monocyte conjugate formation [p = 0.024]). Ticagrelor also significantly attenuated IL-6 release (p = 0.015), reducing peak levels by 43% compared to controls, whereas clopidogrel had a non-significant effect (p = 0.15), with peak levels 28% lower than controls. Conclusion: Ticagrelor inhibited release of pro-inflammatory cytokines TNF and IL-6 in a model of human sepsis. The similar effect of ticagrelor and clopidogrel, as well as the correlation between levels of platelet reactivity and TNF release, suggest that P2Y12 contributes to innate immune response and demonstrates anti-inflammatory effects of P2Y12 inhibition.